2017
DOI: 10.1186/s12014-017-9169-6
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex platform for the identification of ovarian cancer biomarkers

Abstract: BackgroundCurrently, there are no FDA approved screening tools for detecting early stage ovarian cancer in the general population. Development of a biomarker-based assay for early detection would significantly improve the survival of ovarian cancer patients. MethodsWe used a multiplex approach to identify protein biomarkers for detecting early stage ovarian cancer. This new technology (Proseek® Multiplex Oncology Plates) can simultaneously measure the expression of 92 proteins in serum based on a proximity ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 96 publications
3
41
1
Order By: Relevance
“…In agreement with our previous study on the Oncology Iv2 plate (13) and others (25,28), we found high levels of both MK and IL6 in the sera of patients with ovarian cancer. FR-alpha, KLK11, and NECT4 also showed a significant increase in their levels of expression in the sera of ovarian cancer patients as previously reported (24,26,27).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our previous study on the Oncology Iv2 plate (13) and others (25,28), we found high levels of both MK and IL6 in the sera of patients with ovarian cancer. FR-alpha, KLK11, and NECT4 also showed a significant increase in their levels of expression in the sera of ovarian cancer patients as previously reported (24,26,27).…”
Section: Discussionsupporting
confidence: 93%
“…The Proseek platform also includes three "Interplate controls" for data normalization between plates and three "Negative controls" to establish background levels. One microliter of serum from each of the samples was mixed with the Oncology II reagents following the manufacturer's protocol, then processed in combination with the Fluidigm BioMark HD high-throughput PCR instrument at the University of Minnesota Genomics Center as previously described (13). Data generated from the plates were analyzed, including normalization and linearization, per manufacturer's protocol.…”
Section: Sample Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our top-ranked model had a sensitivity of 0.85 and specificity of 0.91 under the same conditions. Similar to the results of these previous studies 8,9 , the performance of our models in the test-proportion of the discovery data is very good, with some models showing perfect classification. We also evaluated the selected models in two replication cohorts and found the performance similar, but somewhat lower than in the discovery set.…”
Section: Discussionsupporting
confidence: 87%
“…We then performed model selection as before based solely on the discovery data (benign tumours versus ovarian cancer stages III-IV) and identified a model consisted of 8 proteins. We finally added three proteins (WFDC2, KRT19 and FR-alpha) based on their previous association with ovarian cancer stages I-II in our modelling, or in previous literature 9,12,13 . The 11-protein panel consisted of MUCIN-16, SPINT1, TACSTD2, CLEC6A, ICOSLG, MSMB, PROK1, CDH3, WFDC2, KRT19 and FR-alpha.…”
Section: Proof-of-concept Model For Practical Usementioning
confidence: 99%